Radiofrequency surgery of the soft palate in the treatment of snoring - a placebo-controlled trial - Stuck, Boris; Sauter, Alexander; Hörmann, Karl; Verse, Thomas; Maurer, Joachim T. (Sleep, 2005)
Recent publications have demonstrated a reduction in snoring with radiofrequency (RF) surgery of the soft palate. Yet so far, all published data has been based on non-controlled trials.Aim of this study was to assess the efficacy of RF surgery of the soft palate in a randomized, placebo-controlled trial.Outpatients department at university hospital, department of otorhinolaryngology26 patients with primary snoring (AHI<15, BMI<35).Patients were treated with temperature-controlled RF surgery of the soft palate under local anesthesia. In accord with a randomization protocol they received 2 sessions of RF surgery (total amount of energy: 3.300 Joule) or placebo (insertion of device needle without energy delivery).Snoring was evaluated by the bed partner with 10 cm visual analogue scales. 23 patients completed the study; 12 received RF-surgery and 11 received placebo. Snoring scores did not change in the placebo group (8.4±1.6 to 8.0±2.3) while improving in the RF-group (8.1±1.3 to 5.2±2.4). The difference between the groups was statistically significant (p<0.05).RF-surgery was significantly better than placebo, although the reduction in snoring was only moderate in our group of patients. This study underlines the necessity for well-controlled clinical trials in the treatment of snoring.